1987
DOI: 10.1523/jneurosci.07-05-01470.1987
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanism of the outward current induced by intracellular injection of inositol trisphosphate into Aplysia neurons

Abstract: Inositol 1,4,5-trisphosphate (InsP3) has been proposed to be the intracellular second messenger in the mobilization of Ca2+ from intracellular stores in a variety of cell types. The ionic mechanism of the effect of intracellularly injected InsP3 on the membrane of identified neurons (R9-R12) of Aplysia kurodai was investigated with conventional voltage-clamp, pressure-injection, and ion-substitution techniques. Brief pressure injection of InsP3 into a neuron voltage- clamped at -40 mV reproducibly induced an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
5
22
0
Order By: Relevance
“…Our results also agree with those of Sawada et al (1987) for the InsP,-activated outward current, and those of Parker and Ivorra (1990b) for chloride currents and Ca, increases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results also agree with those of Sawada et al (1987) for the InsP,-activated outward current, and those of Parker and Ivorra (1990b) for chloride currents and Ca, increases.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, the effect of InsP, in nerve cells ofAplysia kurodai (Sawada et al, 1987) and Aplysia calijbrnica (Sholz et al, 1988) was indirectly shown to mobilize Ca*+, by measuring membrane currents. Fink et al (1988) have shown, using digital imaging of fura-fluorescence, that InsP, increases Ca, in Aplysia bag cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calmodulin is an intracellular Ca21 receptor protein, and is reported to regulate a variety of intracellular processes (Kennedy, 1989;Schulman & Lou, 1989;Hemmings, Nairn, McGuinness, Huganir & Greengard, 1989). The outward current induced by the intracellular injection of InsP3 has been reported to involve a calmodulin-dependent mechanism which opens a potassium channel in Aplysia neurones (Sawada, Ichinose & Maeno, 1987). It has also been suggested that the release of neurotransmitter may be modulated by a calmodulin kinase-mediated phosphorylation of synapsin I (Schulman & Lou, 1989).…”
Section: Effects Of Calmodulin Antagonistsmentioning
confidence: 99%
“…Additional neuronal effects of Ins(1,3,4,5,6)P5 and InsPs have recently been described following their microinjection into identified neurons in the abdominal ganglia of the marine mollusc, Aplysia [202,2031. The injection of InsP6, achieving a calculated intracellular concentration of 0.2 pM, evoked a biphasic response consisting of an initial inward current carried mainly by Na+ and Ca2+, followed by a prolonged hyperpolarisation due to stimulation of an outward K + channel.…”
Section: Inositol13456-pentakisphosphate and Inositol Hexakisphosmentioning
confidence: 99%